Fire Retardant Water Based Clear/Transparent Coating for Wood and Wood Based Interiors - Kumar, Rakesh; Kumar, Aravind; Bhawna (AMC Indian Journal of Civil Engineering, 2025)
This article presents advancement of Fire Retardant Water Based Clear/Transparent Coating for wood and wood based Interiors and the investigation of the equivalent for Reaction to Fire Characteristics" (RTFC). Wood, wood based materials are combustible in nature. When they come in contact of fire, they catch fire easily, spread flames, and increase the heat. Their fire conduct was exceptionally risky or not up to the ideal degree of fire insurance/security. The vast majority of Indian wood when tested to Surface spread of fire tests according to BS–474 section 7, they fall in Class–3 or Class–4, i. e. they give medium or quick fire spread, likewise their Fire propagation index is in range of 30–38. During smoldering and flaming states of fire, combustible materials like wood and wood substitute burst into flames. The present article presents advancement of Fire Retardant Water Based Clear/Transparent Coating for wood and wood based Interiors and the investigation of the equivalent for Reaction to fire characteristics (RTFC). The examination was only focused on the investigation of a powerful and effective synthetic surface barrier. The coating was applied and cured on Shisham wood (SW) and plywood board to assess RTFC according to British standard BS–476 Part 5, 6, and 7 i.e Ignitability test (IT), Fire Propagation Index (FPI) test, and Surface Spread of Flame(SSOF) test. The outcome and charts have been determined and ready for Shisham wood (SW) and Plywood.